2018
DOI: 10.1002/mus.26156
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab in refractory myasthenia gravis: Extended prospective study results

Abstract: Sustained clinical improvement was associated with rituximab after 1 cycle, with prolonged time to relapse and reduction in steroid dosage. Muscle Nerve 58: 453-456, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 19 publications
1
52
0
1
Order By: Relevance
“…Our study showed that CD19 + and CD27 + B cells decreased markedly during the first 3 months. Previous studies demonstrated that antibody titers, NK cells, and CD19 + or CD20 + B cells may not be useful in predicting relapses . However, CD27 + memory B cells may be an effective marker, as shown by a comparative study in which rituximab was administered to patients with refractory MG. CD19 + CD27 + memory B‐cell recovery, but not total CD19 + recovery, was associated with the relapse of clinical symptoms in all patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study showed that CD19 + and CD27 + B cells decreased markedly during the first 3 months. Previous studies demonstrated that antibody titers, NK cells, and CD19 + or CD20 + B cells may not be useful in predicting relapses . However, CD27 + memory B cells may be an effective marker, as shown by a comparative study in which rituximab was administered to patients with refractory MG. CD19 + CD27 + memory B‐cell recovery, but not total CD19 + recovery, was associated with the relapse of clinical symptoms in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that antibody titers, NK cells, and CD19 + or CD20 + B cells may not be useful in predicting relapses. 6,26,27 However, CD27 + memory B cells may be an effective marker, as shown by a comparative study 28 in which rituximab was administered to patients with refractory MG. CD19 + CD27 + memory B-cell recovery, but not total CD19 + recovery, was F I G U R E 3 Changes in lymphocyte subgroups during rituximab treatment (regression curves were generated via the LOESS method; the shadow represents 95% confidence interval around each curve). During rituximab treatment, B cells decreased markedly in the first 3 months and remained at low levels.…”
Section: Discussionmentioning
confidence: 99%
“…Online supplementary file 1 summarises data from selected studies on the use of RTX in AChR-MG. Thirteen studies have been selected, showing good safety 1 2 6 7 9 11–18. The data collected from each report included the number and regimen of infusions used for therapy with RTX, antibody type and titres pretreatment and post-treatment, follow-up duration, data on safety and postintervention status of MG.…”
Section: Resultsmentioning
confidence: 99%
“…The data obtained over the last few years on the use of RTX in refractory MG are heterogeneous in terms of posology, administration scheme and patients’ evaluation. However, previous studies have shown that RTX is safe, since the frequency of serious adverse events is low 2 6–10. The most common side effects are related to the infusion and can be easily prevented by pretreatment with steroids and antihistamines 1 2 9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation